Computational Screening Strategy for Drug Repurposing Identified Niclosamide as Inhibitor of Vascular Calcification - Tanaka, Takeshi; Asano, Takaharu; Okui, Takehito; Kuraoka, Shiori; Singh, Sasha A.; Aikawa, Masanori; Aikawa, Elena (Frontiers in Cardiovascular Medicine, 2022)
Vascular calcification is a cardiovascular disorder with no therapeutic options. We recently reported that o-octanoyltransferase (CROT) suppression can inhibit vascular calcification in vivo and in vitro through amelioration of mitochondrial function and fatty acid metabolism. Inhibiting calcification with a small molecule compound targeting CROT-associated mechanisms will be a promising non-invasive treatment of vascular calcification. Here we used a computational approach to search for existing drugs that can inhibit vascular calcification through the CROT pathway. For screening of the compounds that reduce CROT expression, we utilized the Connectivity Map encompassing the L1000 computational platform that contains transcription profiles of various cell lines and perturbagens including small molecules. Small molecules (n = 13) were identified and tested in human primary smooth muscle cells cultured in osteogenic media to induce calcification. Niclosamide, an FDA-improved anthelmintic drug, markedly inhibited calcification along with reduced alkaline phosphatase activity and CROT mRNA expression. To validate this compound in vivo, LDL receptor (Ldlr)-deficient mice fed a high fat diet were given oral doses of niclosamide (0 or 750 ppm admixed with diet) for 10 weeks. Niclosamide treatment decreased aortic and carotid artery calcification as determined by optical near infrared molecular imaging (OsteoSense680) and histological analysis. In addition, niclosamide improved features of fatty liver, including decreased cholesterol levels along with decreased Crot expression, while plasma total cholesterol levels did not change. Proteomic analysis of aortic samples demonstrated that niclosamide affected wingless/integrated (Wnt) signaling pathway and decreased runt-related transcription factor 2 (Runx2) expression, an essential factor for calcification. Our target discovery strategy using a genetic perturbation database with existing drugs identified niclosamide, that in turn inhibited calcification in vivo and in vitro, indicating its potential for the treatment of vascular calcification.